Serum phosphorylated neurofilament-heavy chain levels in multiple sclerosis patients. Issue 11 (17th March 2014) - Gresle, M M; Liu, Y; Dagley, L F; Haartsen, J; Pearson, F; Purcell, A W; Laverick, L; Petzold, A; Lucas, R M; Van der Walt, A; Prime, H; Morris, D R; et al.
Abstract : Objectives: We evaluated whether the measurement of serum phosphorylated neurofilament heavy chain (pNF-H) titre is likely to be a valid biomarker of axonal injury in multiple sclerosis (MS). Methods: Serum pNF-H concentrations were measured by ELISA in cases with relapsing-remitting (RR)-MS (n=81), secondary progressive (SP) MS (n=13) and primary progressive (PP)-MS; n=6) MS; first demyelinating event (FDE; n=82); and unaffected controls (n=135). A subset of MS cases (n=45) were re-sampled on one or multiple occasions. The Multiple Sclerosis Severity Score (MSSS) and MRI measures were used to evaluate associations between serum pNF-H status, disease severity and cerebral lesion load and activity. Results: We confirmed the presence of pNF-H peptides in serum by ELISA. We showed that a high serum pNF-H titre was detectable in 9% of RR-MS and FDE cases, and 38.5% of SP-MS cases. Patients with a high serum pNF-H titre had higher average MSSS scores and T2 lesion volumes than patients with a low serum pNF-H titre. Repeated sampling of a subset of MS cases showed that pNF-H levels can fluctuate over time, likely reflecting temporal dynamics of axonal injury in MS. Conclusions: A subset of FDE/MS cases was found to have a high serum pNF-H titre, and this was associated with changes in clinical outcome measures. We propose that routine measurement of serum pNF-H should be further investigated for monitoring axonal injury in MS.